Estudo de catalisadores de níquel e ferro suportados em nióbia e sílica na reação de hidrodesoxigenação de guaiacol - Souza, Nina Leão Araújo (2020)
Lignocellulosic biomass is a renewable energy source that has been replacing fossil fuels and can be converted into biofuels and chemicals through thermochemical routes, such as rapid pyrolysis. However, biofuels have a large amount of oxygen, requiring refinement, such as hydrodeoxygenation (HDO), to generate economically favorable compounds for industry. In this work it is proposed to study the HDO of guaiacol, a model compound of lignin widely used due to the methoxy and hydroxyl groups present, in order to identify possible products, a conversion and selectivity for later application in more complex systems. Six catalysts were tested for the HDO reaction, using Ni and Fe as metals and a bimetallic combination Ni-Fe allowed in Nb2O5 (niobium) and in SiO2 (silica). The catalysts were characterized by X-ray diffraction (XRD), Ultraviolet-visible spectroscopy (UV-Vis) and N2 physisorption. With these analyzes it was noted the presence of NiO and Fe2O3 phases in the respective catalysts, predominantly, and a strong interaction between the metals and the support. Low surface areas were obtained, however in accordance with the literature. The catalytic tests showed that for Ni5% catalysts supported on SiO2 and Nb2O5, Fe5% supported on SiO2 and Nb2O5 and Ni5% -Fe5% supported on SiO2 and Nb2O5, the results quite in terms of preparation and of selectivity for phenol, each obtained its particular selectivities, but prevailed as phenol, veratrol and σ-cresol products. Thus, it was observed that the objective when performing a hydrodeoxygenation reaction was found and that there was formation of phenolic compounds using these catalysts, in addition to better understanding the reaction through the qualified routes in the process, such as deoxygenation (DDO), demethylation (DME) and demethoxylation (DMO).